Addressing the compliance gap? UN initiatives to benchmark the human rights performance of states and corporations. Issue 5 (25th November 2015) - HARRISON, JAMES; SEKALALA, SHARIFAH
Abstract: This article examines under what conditions benchmarking and associated measurement initiatives produced by UN human rights actors could, and should, play a role in promoting compliance with international human rights norms. It is organised around a comparative analysis of UN benchmarking initiatives for states and corporations. With regard to states, the article argues that ideological misgivings and technical limitations have so far triumphed over aspirations that indicators and benchmarks might play a significant role in increasing compliance with international human rights norms. With regard to corporations, we find that measuring human rights performance has been framed by the recent UN Guiding Principles on Business and Human Rights using a much more expansive and less quantitative set of benchmarks. These latter benchmarks do not appear to be creating conditions under which the human rights performance of corporations is effectively interrogated, and as a result there is a danger of superficial legitimation. Comparative analysis of these two initiatives reveals some of the tensions inherent in utilising benchmarking in transnational efforts to achieve human rights compliance. It also allows us to contribute to broader debates about the quantification of performance and its potential and limitations as a tool of global governance.